Positive solutions for generalized Hardy-Henon equations - Xizheng Zhang; Xiyou Cheng; Meihua Yang (Electronic Journal of Differential Equations)
This article concerns a generalized Hardy-Henon equation and its associated Dirichlet problem. We obtain upper and lower estimates for positive solutions, and establish the existence and nonexistence of positive solutions to both the equation and its associated Dirichlet problem under certain parametric conditions.